EVI1 expression in early-stage breast cancer patients treated with neoadjuvant chemotherapy - Jonas Leichsenring; Valentina Vladimirova; Christine Solbach; Thomas Karn; Beyhan Ataseven; Bruno Valentin Sinn; Jana Barinoff; Volkmar Müller; Jens-Uwe Blohmer; Christian Schem; Knut Engels; Frederik Marmé; et al. (figshare, 2022)
Abstract Background Overexpression of the EVI1 (ecotropic viral integration site 1) oncogene has recently been implicated as a prognostic factor in breast cancer (BC), particularly in triple-negative BC (TNBC). In this study we aimed to investigate frequency and clinical relevance of EVI1 expression in newly diagnosed BC treated with neoadjuvant chemotherapy. Methods EVI1 expression was determined by immunohistochemistry using H-score as a cumulative measurement of protein expression in pretherapeutic biopsies of BC patients treated with anthracycline/taxane based neoadjuvant chemotherapy within the GeparTrio trial. EVI1 was analyzed as a continuous variable and dichotomized into low or high based on median expression. Endpoints were pathological complete response (pCR), disease-free survival (DFS) and overall survival (OS). Results Of the 993 tumors analyzed, 882 had available subtype information: 50.8% were HR + /HER2-, 15% HR + /HER2 + , 9.8% HR-/HER2 + , and 24.5% TNBC. Median EVI1 H-score was 112.16 (range 0.5–291.4). High EVI1 expression was significantly associated with smaller tumor size (p = 0.002) but not with BC subtype. Elevated EVI1 levels were not significantly associated with therapy response and survival in the entire cohort or within BC subtypes. However, TNBC patients with high EVI1 showed a trend towards increased pCR rates compared to low group (37.7% vs 27.5%, p = 0.114; odds ratio 1.60 (95%CI 0.90–2.85, p = 0.110) and numerically better DFS (HR = 0.77 [95%CI 0.48–1.23], log-rank p = 0.271) and OS (HR = 0.76 [95% 0.44–1.31], log-rank p = 0.314) without reaching statistical significance. Conclusion EVI1 was not associated with response to neoadjuvant therapy or patient survival in the overall cohort. Further analyses are needed to verify our findings especially in the pathological work-up of early-stage HER2-negative BC patients. Trial registration NCT00544765.
Keywords: Medicine; Genetics; Biotechnology; Immunology; Cancer